Widely and Continuously Tunable Continuum Generation From CW-Pumped Cascaded Fibers - Chunyu Guo; Jun Yu; Shuangchen Ruan; Deqin Ouyang; Huaiqin Lin; Weiqi Liu; Yewang Chen; Peiguang Yan; Xuejuan Hu; Ping Hua (IEEE Photonics Journal, 2015)
A tunable continuum with multiwatt output power is demonstrated for the first time through the pumping of cascaded fibers by using a continuous-wave (CW) ytterbium fiber laser. The central wavelength of the output continuum can be tuned continuously and monotonically by varying input pump power, with a wide wavelength-tunable range from 1.2 to 1.4 μm and a 3-dB bandwidth of tens of nanometers. Two configurations of the cascaded fibers both display the power-dependent wavelength tunability. The output spectral characteristics are presented, and the generation of the CW-pumped tunable continuum is tentatively attributed to the seed-dependent Raman amplification.